Decrease of electron paramagnetic defect density and enhancement of electron field emission in annealed carbon films - Lee, YH; Kim, DH; Jang, YT; Ju, BK; Oh, MH (AMER INST PHYSICS, 2000)
We have studied the effect of the paramagnetic defects in carbon films on the field-emission properties. The paramagnetic defects in carbon films originating from the carbon dangling bonds were measured using electron spin resonance (ESR). We found a reduction of the dangling bond density in the annealed carbon films in N-2/H-2 atmosphere from ESR spectroscopy. The annealed films with lower defect densities, i.e., dangling bonds, showed an improved characteristic of higher emission current density as well as a lower turn-on electric field in the Fowler-Nordheim type tunneling. Also in the annealed carbon films a correlation is observed between the decrease of band gap estimated from the electrical conductivity and the reduction of dangling bond density. The earlier results indicate that the enhancement of the emission current level in the annealed carbon films is related to the decrease of the ESR centers. (C) 2000 American Institute of Physics. [S0021-8979(00)05310-X].
Keywords: HYDROGENATED AMORPHOUS-CARBON; VAPOR-DEPOSITED DIAMOND; SPIN-RESONANCE; THIN-FILMS; CATHODES; STATES; ION